2018 AIAA/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2018
DOI: 10.2514/6.2018-1912
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Shape Optimization of the STARC-ABL Concept for Minimal Inlet Distortion

Abstract: The NASA single-aisle turboelectric aircraft with an aft boundary layer propulsor (STARC-ABL) concept utilizes a novel electrically driven aft fan that ingests the fuselage boundary-layer for increased propulsive efficiency. In this paper we examine how aerodynamic shaping of the fuselage diffuser and nacelle inlet can reduce the flow distortion at the aft fan. Adjoint-based aerodynamic shape optimization with the ARP1420 distortion metric objective is used to automatically determine the optimal shapes for min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 23 publications
(19 reference statements)
3
24
0
Order By: Relevance
“…While the axisymmetric models were sufficient to establish the fundamental trends, recent aerodynamic analysis of the STARC-ABL configuration has clearly shown that three-dimensional aerodynamic models are necessary in order to accurately predict the airflow at the aft fuselage. Kenway an Kiris examined the inlet distortion for the BLI propulsor on the aft-fuselage of the STARC-ABL configuration [14], concluding that aerodynamic shape optimization reduced distortion to less than 2%. They performed optimizations of both the bare fuselage and a fuselage with wings attached (but without a vertical tail), finding that the wing downwash has a strong impact on the flow and created additional distortion not present in the fuselage only configuration.…”
Section: Fig 1 Rendering Of the Starc-abl Aircraft Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…While the axisymmetric models were sufficient to establish the fundamental trends, recent aerodynamic analysis of the STARC-ABL configuration has clearly shown that three-dimensional aerodynamic models are necessary in order to accurately predict the airflow at the aft fuselage. Kenway an Kiris examined the inlet distortion for the BLI propulsor on the aft-fuselage of the STARC-ABL configuration [14], concluding that aerodynamic shape optimization reduced distortion to less than 2%. They performed optimizations of both the bare fuselage and a fuselage with wings attached (but without a vertical tail), finding that the wing downwash has a strong impact on the flow and created additional distortion not present in the fuselage only configuration.…”
Section: Fig 1 Rendering Of the Starc-abl Aircraft Configurationmentioning
confidence: 99%
“…This is accomplished via the VSP Preprocessing component in the model, which takes a set of design variables and relates them to the actual OpenVSP model inputs. The ARP1420 Distortion component implements the distortion metric from the "Gas Turbine Engine Inlet Flow Distortion Guidelines" ARP1420 standard [33], using the scheme developed by by Kenway and Keris [14]. The metric captures the magnitude of the variation in total pressure across the fan face both circumferentially and radially using data taken from multiple sensor locations distributed across the fan face.…”
Section: A Optimization Problemmentioning
confidence: 99%
“…They performed a threedimensional adjoint-based aerodynamic shape optimization of the fuselage diffuser and nacelle inlet to minimize inlet distortion at the BLI propulsor. Their results showed that the optimal nacelle and aft-fuselage shape is sensitive to design flight conditions and wing downwash [15]. Building on their previous work, Yildirim and Gray and Gray et al performed geometry optimizations of the three-dimensional NASA STARC-ABL aircraft configuration including vertical tailplane and wing [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…They found that enforcing a constraint on inlet distortion of the fan face reduced the benefits of BLI and the tradeoff between inlet distortion and BLI benefits must be studied further. Kenway and Kiris [8] performed a series of optimizations with the STARC-ABL configuration to minimize the inlet distortion on the BLI fan face. They discovered that the downwash from the wings contribute to the fan face distortion and stated that inclusion of the wings in the models are required to compute the fan face distortion accurately.…”
Section: Introductionmentioning
confidence: 99%